Radiologie und Schwangerschaft: Grundlagen, Rahmenbedingungen und Belastungen - Weisser, Gerald; Steil, Volker; Neff, Wolfgang; Büsing, Karen-Anett (Der Radiologe, 2012)
In a radiology department there are frequently asked questions associated with pregnant and breast feeding women. These are related to either pregnant patients or staff members or the questions are centered on the fetus as a patient. For pregnant patients the potential exposure to the mother and the fetus related to the imaging modality selected as well as the effects of the necessary contrast media must be taken into account. Even for methods without ionizing radiation possible limitations in the use for pregnant women must be discussed. Finally, this medical check defines the imaging modality and the necessary protocol and contrast media. The present article describes the legal requirements in Germany, the technical exposure and pharmacological risks for the pregnant woman and the fetus regarding imaging modalities with and without ionizing radiation. The forthcoming second article will address the risk analysis for examinations with ionizing radiation and will present recommendations for typical clinical imaging problems.
Gesehen am 09.11.2018